Treating Chronic Nonmalignant Pain: Evidence and Faith-Based Approaches. Issue 1 (January 2019) - Snell, Sarah; Hughes, Tia; Fore, Carolyn; Lukman, Roy; Morgan, Brett
Abstract : ABSTRACT: A significant portion of the world's population is impacted by chronic pain; in the United States, chronic pain costs billions annually in treatment and lost productivity. A needs assessment was conducted to evaluate the prevalence of chronic nonmalignant pain (CNMP) at a university occupational therapy clinic over a 3-month period; recommendations were made to improve pain management at the clinic and referring hospital system. Graded Chronic Pain Scale 2.0 results indicated the prevalence of CNMP was a significant problem. Three evidence-based interventions based on the biblically based CREATION Health Model were developed.